PTU-022 Abnormal liver function tests: current time to referral and using iLFTs. (June 2019) - Macpherson, Iain; Priest, Matthew; Dow, Ellie; Dillon, John; Fraser, Andrew
Abstract : Introduction: At present, patients with abnormal LFTs referred to secondary care undergo a serological liver screen and Fibroscan at a nurse-led pre-assessment clinic, before being discussed at a multi-disciplinary team meeting (MDT). The outcome is either advice for management in Primary Care or they are offered an appointment at a consultant clinic. 'Intelligent Liver Function Tests' (iLFTs) provide a diagnostic pathway and stratification for patients with abnormal LFTs in primary care. When requesting iLFTs, the referrer is asked to include alcohol intake, BMI, and if there are features of the metabolic syndrome. Patients with abnormal LFTs on screen undergo reflex testing without further venepuncture or review. We aimed to assess how long it took from initial abnormal liver enzymes to referral to secondary care and compared the outcomes to what would have happened if iLFTs were the initial test. Methods: A retrospective analysis of 93 cases of abnormal LFTsbrought to MDT from February-August 2018 was performed. The MDT result was compared with the diagnosis and outcome had iLFTsbeen used. In addition, the number of times patients had abnormal LFTs and the time period in which the patient had been known to have abnormal LFTs was recorded. Results: 37 patients were referred back to primary care from the MDT. 23 (24.7%) would not have been referred if iLFTs were used. 50 patients were offered review at a consultant clinic. Only 2 (2.1%) patients would not have been referred if iLFTs had been used; both had low fibrosis risks. In 41/50 cases (82%), the diagnosis at MDT was the same if the GP had used iLFTs. 6 patients did not attend for nurse review. 3 (50%) did not require referral if the iLFT protocol had been followed. The median number of times a patient had abnormal LFTs before referral was 5 (min 1; max 33). The median duration of abnormal LFTs before referral was 20 months (min 0; max 87), as shown in figure 1. Conclusions: iLFTs rapidly and safely identify patients with abnormal LFTs requiring referral to secondary care. If iLFTs were used by referrers, 24.7% of patients would not require referral to secondary care. This represents a substantial cost saving in terms of clinic appointments and unnecessary investigations. In addition, patients would be analysed at the time of the first abnormal LFTs, providing referrers information on how to monitor for disease progression and when to refer. This would save significant time in Primary Care, avoiding repeated venepuncture and ensuring patients are referred before they develop end stage liver disease.